Here's the question you clicked on:
Hidden_Twilight
for the function f(x) = sin x, show with the aid of the elementary formula sin^2 A = (1/2)(1 - cos2A) that f(x + y) - f(x) = cos x sin y - 2sin x sin^2(1/2 y)
f(x) = sin x f(x+y)=............
uhm.... I don't get it
|dw:1371559111312:dw|
|dw:1371559308561:dw|
uhm, how did f(x+y) = sin(x+y) happen?
f(x)=sinx, f(x+y)=sin(x+y) replace x+y in place of x.
so f(x) = sin x f(x+y) = sin (x + y) therefore: f(x+y) - f(x) = sin (x+y) - sin x how did sin (x+y) - sin x turned into 2cos (x + [y/2]) sin(y/2)?
you should know the transformations. like |dw:1371560643711:dw|
there are two more in terms of cosine. |dw:1371560779150:dw|